Social networks of educational purpose as a subject of protection in the preparation of specialists of information security - I. D. Rudinskiy; D. Ya. Okolot (Открытое образование (Москва), 2019)
The paper studies application of social networks as a component of the educational information environment of an educational institution in the educational process. The aim of the research is to justify the need to train specialists in the field of information security to provide protection and safe use of social networks in the educational process. To ensure information security of social networks applied in educational processes, it is proposed to incorporate training programs for information security specialists to build their competencies of information security of social networks, including gaining advanced skills to combat new challenging cyber threats, as well as to employ information security specialists with a high level of expertise in cyber security of social networks, determine their work functions in the elaboration of organizational and technical measures to protect users of social networks. In the course of the research, publications on incorporating social networks into the educational process as a didactic tool were analyzed. In particular, on the basis of the conducted analysis of the cited publications and taking into account the authors’ own experience, the properties of social networks that are most promising for their use as a learning platform were determined. However, along with the above positive aspects and advantages, social networks can also be considered as indirect and even direct sources of cyber threats targeted at both the entire educational process and individual users’ accounts. Theoretical and empirical pedagogical methods were used to accomplish the objectives. This facilitated efficient systematization of the collected data for its successful study and identification of the most typical features of the social networks when applied in the educational process and extension of those with specific properties were identified. The paper also describes threats that may arise when using such networks in an educational organization, suggests measures to mitigate risks and discusses functions of information security specialists in ensuring security of social networks used in the educational process. Also, it was established that for the effective and safe use of social networks in the educational process, the organizer of this activity requires specific professional competence in the field of information security, which can be insufficient among the overwhelming majority of lecturers of both general and vocational education. Moreover, a conclusion was drawn about the need to train specialists in the information security of social networks, so they can gain the required professional competences and execute their specific occupations. Proposals were made on the possible development of these competences in the course of studying certain disciplines at the level of the secondary vocational education. Integration of the described approach into the educational process of training information security specialists in institutions of secondary vocational education, aimed at providing maintenance of social networks, will allow meeting the demand for such specialists and, thereby, increasing their competitiveness in the market of educational services.